AI Enabled Healthcare Services During Cross-Border Medical Emergency and Regular Patient Services (ESCORT project): System architecture and first results in Emergency Medicine Scenario - Floros, George; Gui, Daniele; Magalini, Sabina; Martignano, Maurizio; Zellhuber, Incinur; Weber, Michael; Anagnostopoulos, Themistoklis; Lykokanellos, Filopoimin; Tsekeridou, Sofia; Petanidis, Savvas; Chandramouli, Krishna; Markarian, Garik (Proceedings of the International ISCRAM Conference, 2025)
The ESCORT project (ESCORT Project, 2024) aims at connecting up-to-date IoT Wearables, Artificial Intelligence and Machine Learning towards building a framework for a better cross border response for medical emergencies and public health protection and resilience. The ESCORT project brings together healthcare providers from five European member states and one associated member Israel specialized in emergency medicine and offering regular health and care services. New and better integrated digital services have been designed in consultation with stakeholders including patients, patient advocacy groups, health and care service professionals and providers. This paper presents a detailed outline of the project goals and ambitions supplemented by the requirements considered in the development of the overall platform architecture. Out of the 10 tools identified for integration in the project, two will be further elaborated with initial requirements that have been collected, and a first analysis of the solutions will be presented.